(untitled) (Biological Sciences - PJSIR, 2021)
This paper deals with the diffusivity characteristics and the index of activity of ammonium sulfate-sulfur mixture, slow release fertilizer through water. Sulfur used was pure agriculture sulfur as well as sulfur sludge from Abou Zaabal Fertilizer Company. Different practical and theoretical methods were used from which the diffusivity of ammonium sulfate-sulfur mixture through water was found and compared with that of ammonium sulfate fertilizer.